2013
DOI: 10.1159/000350936
|View full text |Cite
|
Sign up to set email alerts
|

Acne Cosmetica Revisited: A Case-Control Study Shows a Dose-Dependent Inverse Association between Overall Cosmetic Use and Post-Adolescent Acne

Abstract: Background: Case-control studies to support the concept of acne cosmetica are lacking. Objective: To examine the association of post-adolescent acne with the use of cosmetics and cosmetic procedures. Methods: 910 post-adolescent patients with acne and an equal number of matched controls were studied for exposure to cosmetics and cosmetic procedures. A cumulative cosmetic exposure index was stratified into four quarters of increasing exposure. Results: Comparison of different cumulative exposure categories with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…A case control study also suggests that overall cosmetic use is negatively linked with post-adolescent acne, but the use of some individual cosmetics have a positive effect with it, not all cosmetics causes acne. 19 No significant association between the type of decorative cosmetics and degree of acne vulgaris was found in this study too. However, the study showed make up foundation was the most frequently used decorative cosmetics.…”
Section: Discussioncontrasting
confidence: 56%
“…A case control study also suggests that overall cosmetic use is negatively linked with post-adolescent acne, but the use of some individual cosmetics have a positive effect with it, not all cosmetics causes acne. 19 No significant association between the type of decorative cosmetics and degree of acne vulgaris was found in this study too. However, the study showed make up foundation was the most frequently used decorative cosmetics.…”
Section: Discussioncontrasting
confidence: 56%
“…The equivocal nature of the results of Singh's study to the other previous studies in this area motivated us toward investigating further on this phenomenon. Moreover, all the above studies focused on adult and postadolescent females while adolescents appeared to be at the peak age of acne prevalence.…”
Section: Introductionmentioning
confidence: 75%
“…Cosmetic usage was assessed using a standard, CCEI available in the literature . Each cosmetic was analyzed in terms of frequency (times per month) and duration of usage (number of months).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The skin’s acid mantle is fundamental to barrier formation and cutaneous antimicrobial defense, and exogenous factors such as detergents, cosmetic products, occlusive dressings, and topical antibiotics could play a role in the pathogenesis of acne by influencing skin pH. 20 , 21 Acne can therefore be considered a multifactorial disease, 22 – 25 and although P. acnes is widely concluded to cause this disease and is thus the main target of most therapeutic protocols, 26 defining a standard treatment regimen is still a great challenge to researchers. 27 Currently, acne can be controlled with appropriate treatment, 1 although improvements may take up to several months, and usually vanish when treatment is withdrawn.…”
Section: Introductionmentioning
confidence: 99%